Earmuff restricts progenitor cell potential by attenuating the competence to respond to self-renewal factors. - Janssens, D.H.; Komori, H.; Grbac, D.; Chen, K.; Koe, C.T.; Wang, H.; Lee, C.Y. (Development, 2014)
Despite expressing stem cell self-renewal factors, intermediate progenitor cells possess restricted developmental potential, which allows them to give rise exclusively to differentiated progeny rather than stem cell progeny. Failure to restrict the developmental potential can allow intermediate progenitor cells to revert into aberrant stem cells that might contribute to tumorigenesis. Insight into stable restriction of the developmental potential in intermediate progenitor cells could improve our understanding of the development and growth of tumors, but the mechanisms involved remain largely unknown. Intermediate neural progenitors (INPs), generated by type II neural stem cells (neuroblasts) in fly larval brains, provide an in vivo model for investigating the mechanisms that stably restrict the developmental potential of intermediate progenitor cells. Here, we report that the transcriptional repressor protein Earmuff (Erm) functions temporally after Brain tumor (Brat) and Numb to restrict the developmental potential of uncommitted (immature) INPs. Consistently, endogenous Erm is detected in immature INPs but undetectable in INPs. Erm-dependent restriction of the developmental potential in immature INPs leads to attenuated competence to respond to all known neuroblast self-renewal factors in INPs. We also identified that the BAP chromatin-remodeling complex probably functions cooperatively with Erm to restrict the developmental potential of immature INPs. Together, these data led us to conclude that the Erm-BAP-dependent mechanism stably restricts the developmental potential of immature INPs by attenuating their genomic responses to stem cell self-renewal factors. We propose that restriction of developmental potential by the Erm-BAP-dependent mechanism functionally distinguishes intermediate progenitor cells from stem cells, ensuring the generation of differentiated cells and preventing the formation of progenitor cell-derived tumor-initiating stem cells.